Recycle of Immobilized Endocellulases in Different Conditions for Cellulose Hydrolysis - Silva, D. F. [UNESP]; Carvalho, A. F.A. [UNESP]; Shinya, T. Y. [UNESP]; Mazali, G. S. [UNESP]; Herculano, R. D. [UNESP]; Oliva-Neto, P. [UNESP] (Hindawi, 2017)
The immobilization of cellulases could be an economical alternative for cost reduction of enzyme application. The derivatives obtained in the immobilization derivatives were evaluated in recycles of paper filter hydrolysis. The immobilization process showed that the enzyme recycles were influenced by the shape (drop or sheet) and type of the mixture. The enzyme was recycled 28 times for sheets E′ and 13 times for drops B′. The derivative E′ showed the highest stability in the recycle obtaining 0.05 FPU/g, RA of 10%, and FPU Yield of 1.64 times, higher than FPU spent or Net FPU Yield of 5.3 times, saving more active enzymes. The derivative B showed stability in recycles reaching 0.15 FPU/g of derivative, yield of Recovered Activity (RA) of 25%, and FPU Yield of 1.57 times, higher than FPU spent on immobilization or Net PFU Yield of 2.81 times. The latex increased stability and resistance of the drops but did not improve the FPU/gram of derivative.